Service functions of agroforestry systems - Beer, John (2003)
This article presents a brief review of the main environmental service functions that are provided by agroforestry systems (AFS): 1) maintenance of soil fertility/reducing erosion via organic matter inputs to the soil, N fixation and nutrient recycling; 2) conservation of water (quantity and quality) via greater infiltration and reduced surface runoff that could contaminate water courses; 3) carbon capture, emphasizing the potential of silvopastoral systems; and 4) biodiversity conservation in fragmented landscapes. These service functions complement the products that AFS provide (commercial and home use; e.g., fuel wood, timber, fruits) but farmers are rarely rewarded for them. More research is needed on the possible tradeoffs between the different service functions when the tree component of agricultural systems is increased; e.g., maximizing carbon capture with high-density tree monocultures will have negative effects on biodiversity conservation. Methods for managing financial incentives, as rewards to farmers who provide these services by adopting/improving AFS, in order to leverage better land use, also have to be developed and tested in different socio economic frameworks. A major limitation to the promotion of AFS is the dearth of economic analyses that include valuation of these service functions.